Life satisfaction and feeling in control: Indicators of successful aging predict mortality in old age - Wiest, Maja; Schüz, Benjamin; Wurm, Susanne (Journal of health psychology, 2012)
Life satisfaction and control beliefs are established indicators of successful aging and predict mortality. However, it has not yet been examined whether they independently predict mortality or interact. We examined main and interaction effects using Cox proportional hazards models in a sample of older adults (N = 1402; age range: 65-91). Only the interaction of life satisfaction and control beliefs significantly predicted mortality when controlling for socio-demographic variables and health. These findings suggest that detrimental effects of low control beliefs can be buffered by life satisfaction, and unexpectedly, that high levels of both factors are not most protective against mortality. © 2012 The Author(s).
Keywords: control beliefs; life satisfaction; mortality; successful aging